Greenhouse gas balance due to the conversion of sugarcane areas from burned to green harvest, considering other conservationist management practices - Bordonal, Ricardo de Oliveira [UNESP]; de Figueiredo, Eduardo Barretto [UNESP]; La Scala, Newton [UNESP] (Wiley-Blackwell, 2012)
There is a growing need for all productive sectors to develop greenhouse gas (GHG) mitigation techniques to reduce the enhanced greenhouse effect. However, the challenge to the agricultural sector is reducing net emissions while increasing production to meet growing demands for food, fiber, and biofuel. This study focuses on the changes in the GHG balance when sugarcane areas are converted from burned harvest (BH) to green harvest (GH, mechanized harvest), including the changes caused by the adoption of conservationist practices such as reduced tillage and a 4-month crop rotation with Crotalaria juncea L. during sugarcane replanting. Based on the Intergovernmental Panel on Climate Change (IPCC) (2006) methodologies, the annual emission balance includes both agricultural and mobile sources of GHG, according to the mean annual consumption of supplies per hectare. The potential soil carbon accumulation was also considered in the GH plot. The total amounts of GHG were 2651.9 and 2316.4 kg CO2eq ha-1 yr-1 for BH and GH, respectively. Factoring in a mean annual soil carbon accumulation rate of 888.1 kg CO2 ha-1 yr-1 due to the input from long-term crop residues associated with the conversion from BH to GH, the emission balance in GH decreased to 1428.3 kg CO2eq ha-1 yr-1. A second decrease occurs when a reduced tillage strategy is adopted instead of conventional tillage during the replanting season in the GH plot, which helps reduce the total emission balance to 1180.3 kg CO2eq ha-1 yr-1. Moreover, the conversion of sugarcane from BH to GH, with the adoption of a crop rotation with Crotalaria juncea L. as well as reduced tillage during sugarcane replanting, would result in a smaller GHG balance of 1064.6 kg CO2eq ha-1 yr-1, providing an effect strategy for GHG mitigation while still providing cleaner sugar and ethanol production in southern Brazil.
Keywords: bioenergy; Crop rotation; ethanol production; global warming; inventory; mitigation; reduced tillage